CLASSIFICATION OF TOPONYMS AND REFLECTION OF HISTORICAL INFORMATION - Shakhzod Eshankulov (Western European Studies, 2025)
The article examines the classification of toponyms and the reflection of historical information within them. It provides a comprehensive analysis of the main typological categories of geographical names, their linguistic and semantic features, as well as the historical, ethnographic, and cultural data encoded in toponymic structures. The study highlights how toponyms serve as reliable historical sources that preserve information about ancient settlements, ethnic composition, social relations, and economic activities of different periods. Special attention is given to methodological approaches in the classification of toponyms according to their origin, structure, and meaning
Keywords: Toponymy; toponym classification; historical geography